LONG-TIME INVESTIGATION OF CEMENT COMPOSITE MATERIAL WITH MICRONIZED WASTE MARBLE POWDER: DYNAMIC MODULES - Zdeněk Prošek; Jaroslav Topič (Acta Polytechnica CTU Proceedings)
This article focus on “blended cement”. The blended cement was created by using waste marble powder (WMP) as a partial replacement for cement. We investigated the influence of WMP on the developing of the dynamic modulus of elasticity and the dynamic shear modulus in time. Four different cement composites with WMP as a partial replacement for cement were studied (5, 10, 15 and 50 wt. %) together with reference samples. Dynamic modulus of elasticity was monitored during the first 377 days since manufacture by use of non-destructive testing (resonance method). The results showed that WMP in a small amount had a no effect on the dynamic modulus of elasticity and the dynamic shear modulus.